Composite wave-absorbing material as well as preparation method and application thereof

By using the composite absorbing material of high -entropilic iron alloy with high -entropy iron oxygen body and body heart cube structure, the problem of insufficient performance of electromagnetic wave absorption materials in existing technologies, realizing high -efficiency electromagnetic wave absorption, reducing Electromagnetic pollution.

CN119383941AInactive Publication Date: 2025-01-28NANCHANG UNIV

Patent Information

Application Number
CN202411962411.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to develop high-performance electromagnetic wave absorbing materials in the prior art, especially in terms of thin matching thickness, strong absorption performance and absorption frequency bandwidth, which has led to the problem of electromagnetic pollution that has not been effectively solved.

Method used

The composite absorbing material of the high -entropyed iron alloy with a high -entropy iron oxygen body and the cubic structure of the heart -hearted cubic structure adopts a composite absorbing material of the high -entropy iron alloy in the center of heart. Composite suction material with excellent suction performance.

Benefits of technology

The effective absorption of electromagnetic waves has the advantages of matching thickness, strong absorbing performance, and absorbing frequency bandwidth, which can effectively reduce electromagnetic pollution and avoid secondary pollution caused by reflecting electromagnetic waves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119383941A_ABST
    Figure CN119383941A_ABST
Patent Text Reader

Abstract

The invention provides a composite wave-absorbing material as well as a preparation method and application thereof, and relates to the technical field of wave-absorbing materials. The composite wave-absorbing material provided by the invention has high-entropy ferrite with a spinel structure and high-entropy iron alloy with a body-centered cubic structure, the chemical formula of the high-entropy ferrite is (CoxNiyCuzMnaZnbMgcCrd) Fe2O4, x + y + z + a + b + c + d = 1, x, y and z are real numbers greater than 0 and less than 1, a, b, c and d are real numbers greater than or equal to 0 and less than 1, and two or three of a, b, c and d are equal to 0. The composite wave-absorbing material provided by the invention has the advantages of thin matching thickness, strong wave-absorbing performance and wide absorption frequency band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of absorbing materials, and in particular to a composite absorbing material and a preparation method and application thereof. Background Art

[0002] With the rapid development of electronic communication technology, the increasing popularity of electronic products has brought great convenience to people's lives, but the resulting electromagnetic pollution problem has also become increasingly serious. The generation of too many redundant electromagnetic waves will not only interfere with the normal operation of precision instruments and equipment, but may also pose a threat to human health.

[0003] Electromagnetic wave absorbing materials are materials that have high absorption, low transmission, and low reflection characteristics for electromagnetic waves, and can convert the energy of absorbed electromagnetic waves into energy in the form of heat and other forms of energy for consumption. This material can effectively avoid the secondary pollution problem that may be caused by reflected electromagnetic waves caused by electromagnetic shielding. Therefore, the research and development of high-performance absorbing materials is the key to improving the problem of electromagnetic pollution. Summary of the invention

[0004] The object of the present invention is to provide a composite absorbing material and a preparation method and application thereof, which has the advantages of thin matching thickness, strong absorbing performance and wide absorption bandwidth, and can effectively absorb electromagnetic waves.

[0005] In a first aspect, the present invention provides a composite absorbing material having a high entropy ferrite with a spinel structure and a high entropy iron alloy with a body-centered cubic structure, and the chemical formula of the high entropy ferrite is (Co x Ni y Cu z Mn a Zn b Mg c Cr d )Fe2O4, where x+y+z+a+b+c+d=1, x, y, z are all real numbers greater than 0 and less than 1, a, b, c, d are all real numbers greater than or equal to 0 and less than 1, and two or three of a, b, c, d are equal to 0.

[0006] In a second aspect, the present invention further provides a method for preparing a composite absorbing material, comprising: mixing metal oxide raw materials in a solid phase and then calcining them, and then annealing them at a high temperature in a reducing atmosphere to obtain the composite absorbing material.

[0007] Optionally, the metal oxide raw material includes cobalt oxide, nickel oxide, copper oxide and iron oxide, and also includes one or two of manganese oxide, zinc oxide, magnesium oxide and chromium oxide.

[0008] Optionally, the method comprises the following steps: mixing metal oxide raw materials in a solid phase to obtain a mixed powder; molding the mixed powder and calcining the mixed powder to obtain a composite intermediate; and annealing the composite intermediate at a high temperature in a reducing atmosphere to obtain a composite absorbing material.

[0009] Optionally, the metal oxide raw materials are ball milled and mixed.

[0010] Optionally, the mass ratio of the metal oxide raw material to the ball milling balls during ball milling is 1:(1-10).

[0011] Optionally, the metal oxide raw material is mixed with a grinding aid and ball-milled, and the grinding aid includes anhydrous ethanol.

[0012] Optionally, the metal oxide raw material is ball-milled and mixed for 3 h to 8 h.

[0013] Optionally, the mixed powder is formed into a compact under a pressure of 10 MPa-20 MPa.

[0014] Optionally, the mixed powder is formed into a compact and then calcined at 1000°C-1200°C.

[0015] Optionally, the mixed powder is formed into a compact and then calcined for 3 h to 8 h.

[0016] Optionally, after the mixed powder is formed into a compact, the temperature is increased at a rate of 1° C. / min-10° C. / min and calcined.

[0017] Optionally, the volume fraction of hydrogen in the reducing atmosphere is 10%-100%.

[0018] Optionally, the reducing atmosphere includes an inert carrier gas, and the inert carrier gas includes one of helium, argon and neon.

[0019] Optionally, the composite intermediate is heated to an annealing temperature at a rate of 1° C. / min-10° C. / min in a reducing atmosphere and subjected to high-temperature annealing.

[0020] Optionally, the composite intermediate is annealed at 700°C-900°C.

[0021] Optionally, the composite intermediate is annealed at high temperature in a reducing atmosphere for 2-5 h.

[0022] In a third aspect, the present invention further provides an application of any of the above optional composite absorbing materials or a composite absorbing material prepared by any of the above optional preparation methods, wherein the application includes electromagnetic absorbing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is a flowchart of a method for preparing a composite absorbing material in an embodiment of the present invention; Figure 2The XRD characterization diagrams of the composite absorbing materials prepared in Examples 1 to 6 of the present invention; Figure 3 This is a SEM image of the HE-4 composite absorbing material prepared in Example 4 of the present invention; Figure 4 This is a SEM image of the HE-5 composite absorbing material prepared in Example 5 of the present invention; Figure 5 This is a wave absorbing performance curve diagram of the HE-1 composite wave absorbing material prepared in Example 1 of the present invention; Figure 6 This is a curve diagram of the wave absorbing performance of the HE-2 composite wave absorbing material prepared in Example 2 of the present invention; Figure 7 This is a wave absorbing performance curve diagram of the HE-3 composite wave absorbing material prepared in Example 3 of the present invention; Figure 8 This is a curve diagram of the wave absorbing performance of the HE-4 composite wave absorbing material prepared in Example 4 of the present invention; Fig. 9 This is a curve diagram of the wave absorbing performance of the HE-5 composite wave absorbing material prepared in Example 5 of the present invention; Fig.10 This is a curve diagram of the wave absorbing performance of the HE-6 composite wave absorbing material prepared in Example 6 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0025] The present invention provides a method for preparing a composite absorbing material, comprising: mixing metal oxide raw materials in solid phase and then calcining them, and then annealing them at high temperature in a reducing atmosphere to obtain the composite absorbing material. In fact, by calcining the metal oxides in solid phase, a high entropy oxide with a spinel structure can be obtained, and after high temperature annealing in a reducing atmosphere, an iron alloy with a body-centered cubic structure can be generated in the high entropy oxide, thereby obtaining the composite absorbing material.

[0026] Specifically, the metal oxide raw materials include cobalt oxide, nickel oxide, copper oxide, iron oxide, and one or two of manganese oxide, zinc oxide, magnesium oxide, and chromium oxide. In fact, after solid phase mixing and calcination, the high entropy oxide obtained is high entropy ferrite, which can be expressed as AB2O4, wherein the A phase is a mixed phase of the remaining metal oxides except iron oxide (Fe2O3), and the iron oxide (Fe2O3) is the B phase.

[0027] Specifically, the cobalt oxide includes one of CoO, Co2O3, and Co3O4, the nickel oxide includes one of NiO and Ni2O3, the copper oxide includes one of CuO and Cu2O, the iron oxide includes Fe2O3, the manganese oxide includes MnO, the zinc oxide includes ZnO, the magnesium oxide includes MgO, and the chromium oxide includes Cr2O3.

[0028] In some embodiments, see Figure 1 The preparation method of the composite absorbing material comprises the following steps: S1, mixing metal oxide raw materials in a solid phase to obtain a mixed powder; S2, forming the mixed powder into a blank and then calcining it to obtain a composite intermediate; S3. The composite intermediate is annealed at high temperature in a reducing atmosphere to obtain a composite absorbing material.

[0029] In fact, when executing step S1, the metal oxide raw materials are ball-milled and mixed, which is beneficial for sufficient collision and uniform dispersion of the metal oxide raw materials, and is beneficial for improving the dispersion uniformity of each metal element in the obtained mixed powder. At the same time, it can improve the uniformity of the particle size of each metal oxide raw material in the mixed powder, which is beneficial for sintering in step S2.

[0030] In addition, when executing step S1, the metal oxide raw material and the grinding aid can be mixed in advance to improve the mixing effect when the metal oxide raw material is ball-milled. In fact, the grinding aid includes anhydrous ethanol. By mixing anhydrous ethanol with the metal oxide raw material and then ball-milling, the grinding uniformity during the ball milling process can be improved. At the same time, the anhydrous ethanol can be effectively removed by drying after grinding to avoid contamination of the mixed powder.

[0031] In some embodiments, when performing ball milling on the metal oxide raw material in step S1, the mass ratio of the metal oxide raw material to the ball milling balls is controlled to be 1: (1-10), so that the ball milling balls and the metal oxide raw material can fully collide and squeeze during the ball milling process, thereby obtaining a mixed powder with uniform particle size and uniform dispersion. Specifically, the ball milling balls can be made of zirconium oxide. In addition, when ball milling the metal oxide raw material, the ball milling time is controlled to be 3h-8h.

[0032] In fact, the mixed powder is formed into a blank in step S2, which can effectively improve the compactness between the mixed powders, thereby facilitating the formation of a structurally stable composite intermediate after calcination, and promoting the formation of a spinel structure in the composite intermediate. Specifically, the mixed powder is formed into a blank under a pressure of 10MPa-20MPa, which is conducive to shaping the mixed powder.

[0033] In some embodiments, when the mixed powder is formed into a green body in step S2, the diameter of the green body obtained can be 10 mm-20 mm, which is conducive to uniform calcination and molding of the green body during the calcination process. In addition, during the green body forming process, the mixed powder can be filled into a mold, and pressure is applied to the mold to complete the green body molding.

[0034] In some embodiments, after the mixed powder is formed into a green body in step S2, it is calcined at 1000°C-1200°C, so that the green body can be sintered and a high entropy ferrite with a spinel structure can be obtained. In addition, the sintering time of the green body can be controlled to be 3h-8h, and the green body can be sintered uniformly. Specifically, after the mixed powder is formed into a green body in step S2, the obtained green body is heated and calcined in an air atmosphere. In fact, the heating rate can be controlled to be 1°C / min-10°C / min.

[0035] In fact, by subjecting the composite intermediate to a high temperature annealing treatment in a reducing atmosphere in step S3, a composite absorbing material having a spinel structure and a body-centered cubic structure can be obtained. Meanwhile, different element compositions in the composite intermediate can affect the relative contents of the spinel structure and the body-centered cubic structure in the composite absorbing material, thereby affecting the absorbing performance of the obtained composite absorbing material.

[0036] Specifically, the volume fraction of hydrogen in the reducing atmosphere used in step S3 is 10%-100%, and the reducing atmosphere also includes an inert carrier, wherein the inert carrier gas includes one of helium, argon, and neon. In fact, when the composite intermediate is subjected to high-temperature annealing, the composite intermediate can be placed in a tubular furnace in advance, and the tubular furnace can be gas-displaced with a reducing atmosphere, and then the temperature is raised to 700°C-900°C at a rate of 1°C / min-10°C / min and kept warm for 2h-5h.

[0037] In addition, the present invention also provides a composite absorbing material prepared by any of the above preparation methods, wherein the composite absorbing material comprises a high entropy ferrite with a spinel structure and a high entropy iron alloy with a body-centered cubic structure, and the chemical formula of the high entropy ferrite is (Co x Ni y Cu z Mn a Zn b Mg c Crd )Fe2O4, where x+y+z+a+b+c+d=1, x, y, z are all real numbers greater than 0 and less than 1, a, b, c, d are all real numbers greater than or equal to 0 and less than 1, and two or three of a, b, c, d are equal to 0.

[0038] The present invention also provides an application of a composite absorbing material prepared by any of the above preparation methods, one of the applications of which can be electromagnetic absorbing. In fact, the preparation method of the composite absorbing material provided by the present invention has a simple process and a high success rate, and does not require the use of complex equipment and a complex process environment. The prepared composite absorbing material has the advantages of thin matching thickness, strong absorbing performance and wide absorption bandwidth.

[0039] Example 1

[0040] This embodiment 1 provides a method for preparing a composite absorbing material, comprising the following steps: S1. Weigh 0.06 mol (9.5814 g) of Fe2O3, 0.015 mol (1.1239 g) of CoO, 0.015 mol (1.1203 g) of NiO, 0.015 mol (1.1932 g) of CuO, and 0.015 mol (1.0641 g) of MnO, mix a total of 14.0829 g of the metal oxide mixture with 20 mL of anhydrous ethanol and put it into a ball mill, add 42 g of zirconium oxide ball milling balls, and mill at a speed of 300 rpm for 6 h. Take it out and dry it in a drying oven at 90 ° C for 10 h to obtain a mixed powder; S2, taking 0.6g of the mixed powder and putting it into a circular mold with a diameter of 12mm, using a tablet press to apply a pressure of 10MPa for 180s to obtain a green body, and placing the green body in a muffle furnace, heating it to 1150℃ at a rate of 5℃ / min in an air atmosphere and keeping it at that temperature for 5h, and then cooling it to room temperature with the furnace to obtain a composite intermediate; S3. Place the composite intermediate in a tubular furnace, introduce a hydrogen-argon mixed gas (hydrogen concentration 10% and the remainder argon) into the tubular furnace for gas replacement, and then heat the tubular furnace to 800°C at a rate of 5°C / min; keep warm for 3 hours and then cool to room temperature to obtain a composite absorbing material (HE-1).

[0041] Example 2

[0042] This embodiment 2 provides a method for preparing a composite absorbing material, which is different from the embodiment 1 in that: in step S1, 0.015 mol (1.2208 g) of ZnO is weighed to replace MnO; in step S2, the tablet press applies a pressure of 20 MPa for 120 s; and in step S3, the composite absorbing material (HE-2) is obtained.

[0043] Example 3

[0044] This embodiment 3 provides a method for preparing a composite absorbing material, which is different from that of embodiment 1 in that: in step S1, 0.015 mol (0.6045 g) of MgO is weighed to replace MnO; in step S2, a tablet press applies a pressure of 15 MPa for 150 s; and in step S3, a composite absorbing material (HE-3) is obtained.

[0045] Example 4

[0046] This embodiment 4 provides a method for preparing a composite absorbing material, which is different from the embodiment 1 in that: in step S1, 0.0075 mol (1.1399 g) of Cr2O3 is weighed to replace MnO; in step S3, a composite absorbing material (HE-4) is prepared.

[0047] Example 5

[0048] This embodiment 5 provides a preparation method of a composite absorbing material, which is different from the embodiment 1 in that: in step S1, 0.06 mol (9.5814 g) of Fe2O3, 0.012 mol (0.8991 g) of CoO, 0.012 mol (0.8962 g) of NiO, 0.012 mol (0.9546 g) of CuO, 0.012 mol (0.8512 g) of MnO, and 0.012 mol (0.4836 g) of MgO are weighed; in step S3, a composite absorbing material (HE-5) is prepared.

[0049] Example 6

[0050] This embodiment 6 provides a method for preparing a composite absorbing material, which is different from the embodiment 1 in that: in step S1, 0.06 mol (9.5814 g) of Fe2O3, 0.012 mol (0.8991 g) of CoO, 0.012 mol (0.8962 g) of NiO, 0.012 mol (0.9546 g) of CuO, 0.012 mol (0.8512 g) of MnO, and 0.006 mol (0.9119 g) of Cr2O3 are weighed; in step S3, a composite absorbing material (HE-6) is prepared.

[0051] Phase analysis

[0052] The composite absorbing materials (HE-1 to HE-6) prepared in Examples 1 to 6 were ground into composite absorbing powders, and then the phase compositions of the composite absorbing powders were characterized by using an X-ray diffraction system (XRD, D8-Advanced, Bruker, Germany) with Cu-Kα radiation (λ=1.5418Å), and compared with the standard PDF cards of ferroalloys (JCPDS No.87-0722) and ferroferric oxide (JCPDS No.19-0629). Figure 2 shown.

[0053] from Figure 2 It can be seen that although the composition elements in the composite absorbers HE-1 to HE-6 are different, they all show high entropy oxides and a second phase (iron alloy), and this second phase has a body-centered cubic lattice and belongs to the Im_3m (229) space group. Its main diffraction peaks are (110) crystal plane (44.76°) and (211) crystal plane (82.53°). This shows that after reduction treatment in a reducing atmosphere, an iron alloy with a body-centered cubic structure can be generated in the high entropy spinel lattice. In addition, with the different elemental compositions in different composite absorbers, the intensity of the characteristic peaks of the spinel structure also varies significantly.

[0054] After the composite absorbing materials (HE-4 and HE-5) prepared in Example 4 and Example 5 were ground into composite absorbing powders, the morphologies of the composite absorbing powders were observed using a field emission scanning electron microscope (SEM, Sigma 300VP, Zeiss, German). The specific operations included: laminating the conductive adhesive on the sample stage of the scanning electron microscope in advance, transferring a small amount of the composite absorbing powder onto the conductive adhesive, performing gold spraying treatment using an ion sputtering instrument, and observing the microscopic morphology, as shown in FIG. Figure 3 and Figure 4 shown.

[0055] from Figure 3 It can be seen that the HE-4 composite absorbing material prepared in Example 4 presents a porous and granular structure and has a certain number of pores inside, which is conducive to the rapid attenuation of electromagnetic waves. Figure 4 It can be seen that the HE-5 composite absorbing material prepared in Example 5 is composed of a number of fine particles, and its particle size is larger than that in Example 4, and the pores inside are also conducive to the rapid attenuation of electromagnetic waves.

[0056] Wave absorption performance test

[0057] The composite absorbing materials (HE-1 to HE-6) prepared in Examples 1 to 6 were ground into composite absorbing powders, heated and mixed with paraffin wax at a mass ratio of 7:3, and then pressed into a circular absorber with an outer diameter of 7.00 mm, an inner diameter of 3.04 mm, and a thickness of 2.0 mm. The relative complex dielectric constants ( ) and relative complex permeability ( ), and according to the measured data, the following planning formula is substituted to calculate the absorption performance curves at thicknesses of 1.0mm, 1.4mm, 1.8mm, 2.2mm, 2.6mm, 3.0mm, 3.4mm, 3.8mm, 4.2mm, 4.6mm, 5.0mm, and 5.5mm, respectively. Figures 5 to 10 As shown, the planning formula is: ; ; in, is the characteristic impedance of free space - 376.73Ω, is the input impedance of the absorber, is the frequency of the electromagnetic wave (2GHz-18GHz), is the absorber thickness, is the speed of light in free space — 3×10 8 m / s.

[0058] from Figure 5 It can be seen that when the HE-1 composite absorbing material prepared in Example 1 is composed of Fe, Co, Ni, Cu, Mn and O, its maximum reflection loss reaches -21.77 dB when the thickness of the absorbing coating is only 1.8 mm, and the effective absorbing bandwidth (reflection loss is less than -10 dB, representing 90% electromagnetic wave absorption) reaches 4 GHz (13.28-17.28 GHz), covering 50% of the Ku band.

[0059] from Figure 6 It can be seen that when the HE-2 composite absorbing material prepared in Example 2 is composed of Fe, Co, Ni, Cu, Zn, and O, its maximum reflection loss reaches -25.99 dB when the thickness of the absorbing coating is 5.5 mm, and its effective absorbing bandwidth reaches 4.64 GHz (11.92 GHz-16.56 GHz) when the thickness of the absorbing coating is 1.5 mm.

[0060] from Figure 7It can be seen from the figure that the HE-3 composite absorbing material prepared in Example 3 has poor absorbing performance when the constituent elements are Fe, Co, Ni, Cu, Mg, and O, and its reflection loss value is above -10 dB; Figure 8 It can be seen that the HE-4 composite absorbing material prepared in Example 4, when the constituent elements are Fe, Co, Ni, Cu, Cr, and O, exhibits excellent electromagnetic absorbing performance, with a maximum reflection loss of -50.92 dB, when the absorbing coating thickness is 1.7 mm, and the effective absorbing bandwidth reaches 5.12 GHz (12.72 GHz-17.84 GHz) when the absorbing coating thickness is 1.3 mm, covering 85% of the Ku band, which indicates that the introduction of the Cr element is more conducive to the electromagnetic wave absorption of the material system compared to HE-1 to HE-3.

[0061] from Fig. 9 It can be seen that the HE-5 composite absorbing material prepared in Example 5 exhibits more excellent electromagnetic absorbing performance when the constituent elements are Fe, Co, Ni, Cu, Mn, Mg, and O. The thickness of the absorbing layer is 1.5 mm, the maximum reflection loss is -48.77 dB, and the effective absorbing bandwidth reaches 6.08 GHz (11.92 GHz-18 GHz), achieving full coverage of the Ku band. This shows that the introduction of Mn and Mg elements greatly enhances the absorbing performance of the material system.

[0062] from Fig.10 It can be seen that the HE-6 composite absorbing material prepared in Example 6 also exhibits excellent electromagnetic absorbing performance when the constituent elements are Fe, Co, Ni, Cu, Mn, Cr, and O. When the thickness of the absorbing layer is 1.9 mm, the maximum reflection loss is -46.84 dB, and when the thickness of the absorbing coating is 1.4 mm, the effective absorbing bandwidth reaches 4.72 GHz (12.4 GHz-17.12 GHz). Compared with HE-1 to HE-3, the introduction of Mn and Cr elements can significantly enhance the absorbing performance of the absorbing material.

[0063] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A composite absorbing material, characterized in that: A high entropy ferrite having a spinel structure and a high entropy iron alloy having a body-centered cubic structure, wherein the chemical formula of the high entropy ferrite is (Co x Ni y Cu z Mn a Zn b Mg c Cr d )Fe2O4, where x+y+z+a+b+c+d=1, x, y, z are all real numbers greater than 0 and less than 1, a, b, c, d are all real numbers greater than or equal to 0 and less than 1, and two or three of a, b, c, d are equal to 0.

2. A method for preparing the composite absorbing material as claimed in claim 1, characterized in that: include: The metal oxide raw materials are mixed in solid phase and then calcined, and then annealed at high temperature in a reducing atmosphere to obtain a composite wave absorbing material.

3. The preparation method according to claim 2, characterized in that: The metal oxide raw materials include cobalt oxide, nickel oxide, copper oxide and iron oxide, and also include one or two of manganese oxide, zinc oxide, magnesium oxide and chromium oxide.

4. The preparation method according to claim 2, characterized in that: The following steps are involved: The metal oxide raw materials are mixed in the solid phase to obtain a mixed powder; the mixed powder is formed into a blank and then calcined to obtain a composite intermediate; the composite intermediate is annealed at a high temperature in a reducing atmosphere to obtain a composite wave absorbing material.

5. The preparation method according to claim 4, characterized in that: The metal oxide raw material is ball-milled and mixed; wherein: the mass ratio of the metal oxide raw material to the ball milling ball during ball milling is 1:(1-10); and / or, the metal oxide raw material is mixed with a grinding aid and ball-milled, wherein the grinding aid includes anhydrous ethanol; and / or, the metal oxide raw material is ball-milled and mixed for 3h-8h.

6. The preparation method according to claim 4, characterized in that: The mixed powder is formed into a blank under a pressure of 10MPa-20MPa; and / or, the mixed powder is calcined at 1000°C-1200°C after being formed into a blank; and / or, the mixed powder is calcined for 3h-8h after being formed into a blank; and / or, the mixed powder is heated and calcined at a rate of 1°C / min-10°C / min after being formed into a blank.

7. The preparation method according to claim 4, characterized in that: The volume fraction of hydrogen in the reducing atmosphere is 10%-100%; and / or, the reducing atmosphere includes an inert carrier gas, and the inert carrier gas includes one of helium, argon, and neon; and / or, the composite intermediate is heated to an annealing temperature at a rate of 1°C / min-10°C / min in the reducing atmosphere and high-temperature annealed; and / or, the composite intermediate is annealed at 700°C-900°C; and / or, the composite intermediate is annealed at high temperature in the reducing atmosphere for 2h-5h.

8. An application of the composite absorbing material according to claim 1 or the composite absorbing material prepared by the preparation method according to any one of claims 2 to 7, characterized in that: The applications include electromagnetic wave absorption.

Citation Information

Patent Citations

  • Ferrite / metal oxide material and preparation method and application thereof

    CN106140173A

  • High-entropy oxide ceramic, preparation method thereof and application of high-entropy oxide ceramic as electromagnetic wave absorbing material

    CN114736010A

  • High-temperature-resistant high-entropy metal ceramic wave-absorbing filler and preparation method thereof

    CN116949336A

Cited By

  • ZrB2-SiC hollow rod composite material, preparation method and application

    CN120309368A

  • High-entropy spinel oxide synthesized by carbon thermal shock method as well as preparation method and application of high-entropy spinel oxide

    CN121672596A